RETHINKING THE ADOPTION OF GREEN BUILDING RATING SYSTEMS IN DEVELOPING COUNTRIES - Veronica Soebarto; David Ness (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2011)
This paper critically reviews the adoption of green building rating systems in developing countries such as Indonesia. Most new buildings in Indonesian cities are replacing the already socially-vibrant urban kampungs; however, green building rating systems do not assess environmental, social and economic impacts upon the existing communities. The paper compares the motivation and approaches of the green building movement and green rating tools with the philosophies and implementation of the urban kampung improvement programme (KIP), implemented for years to improve the condition of Indonesia’s urban kampungs. Ideas and the means for developing more sociallyresponsible green developments are presented and a closer integration of KIP with ‘green’ urban development is recommended.